If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60 + 5n = 2n Solving 60 + 5n = 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. 60 + 5n + -2n = 2n + -2n Combine like terms: 5n + -2n = 3n 60 + 3n = 2n + -2n Combine like terms: 2n + -2n = 0 60 + 3n = 0 Add '-60' to each side of the equation. 60 + -60 + 3n = 0 + -60 Combine like terms: 60 + -60 = 0 0 + 3n = 0 + -60 3n = 0 + -60 Combine like terms: 0 + -60 = -60 3n = -60 Divide each side by '3'. n = -20 Simplifying n = -20
| 5x-10=5(x+4) | | 5w-27=28 | | 4=-2g | | .4n=12 | | -x/24=4 | | 2c+(3c+-4)=5c+-4 | | 6=r-7 | | y=9x+3x | | Z-5-13= | | X+(-8)=-16 | | 3y+15=36 | | 2c+(3c+-4)=4c+-4 | | -4(n+2)=-5n | | (8x^4y^2/3z^3)*(9xy^2z^6/4y^4) | | 1.21=11(0.5+0.4x)whatisx | | -33/4x=-60 | | 12*x=132 | | 8+4v+8v+5=1+8v | | (8x^4y^2/3z^3)*(9xy^2z^6) | | 4a+3b+8-2a-3b= | | 3x-54=44+10x | | 5x+4-x=4+3x-4 | | 3(x-6)=4x-x+2 | | 7x+9=x-3y | | 2x+(2b-1)y=4 | | 23-48x=82x+56 | | -4-3(x-5)=12x+2(x-3) | | -44+x=20 | | Hb-3v=0 | | 5(x-5)=5x+12 | | H=3v/b | | 2=(x-2.1)/1.3 |